Politik Islam di Indonesia Pasca Kemerdekaan Hingga Demokrasi Terpimpin - Ma’afi, Rif’at Husnul (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2013)
Abstract: This article describes about the Islamic political development in Indonesia after its independence to the guided democracy. In the early days of its independence, there was a debate among Islamists and nationalists in formulating legislation until they agreed upon the first principle âBelief in one Godâ. At the time of parliamentary democracy, many Islamic organizations established a political party and participated in the general election in 1955, including Masjumi, NU, PSII and Perti. At the time of the guided democracy, there were two groups of the Islamic party. The first group was Masjumi which viewed that the participation in the authoritarian political system as a deviation from Islamic teachings. The second group was the Muslim League (NU, PSII and Perti). They argued that participating in the guided democracy was a realistic and pragmatic attitude. The destruction of the Guided Democracy occurred after a mutiny by PKIâs movement on September 30th, 1965. With the expiration of the Guided Democracyâs period then ended the old order and changed into the new order under the Suhartoâs power. This resulted a change in Islamic politics in Indonesia.Keywords: Islam, post-independence, guided democracy